Prevention of implant-associated spinal infections: the GAID-protocol - Przybyl, Joanna Maria; Hegewald, Aldemar Andres (Frontiers in Surgery, 2023)
The purpose of this study is to investigate the efficacy of the GAID-Protocol, a bundle of intra-and postoperative infection prevention measures, to reduce implant-associated infections in patients undergoing posterior spinal fusion with instrumentation. These preventive measures are organized into a protocol that includes recommendations for four critical areas of implant protection (acronym GAID): Gloves, Antiseptics: sodium hypochlorite/hypochlorous acid (NaOCl/HOCl), Implants and Drainage-use in large wounds.We performed a single-site retrospective review of cases undergoing posterior spinal fusion with instrumentation for primarily degenerative spinal diseases before and after implementation of the GAID-Protocol that was specifically designed to protect against implantassociated infections. The primary outcome was postoperative wound complications requiring surgical intervention, with a particular focus on infectious spondylitis/discitis.Results: 230 cases were included: 92 (Group A) before and 138 (Group B) after protocol implementation. Overall, wound complications requiring surgical intervention occurred in 7.6% patients in Group A and in 3.6% patients in Group B (p = 0.2297). Of these, infectious spondylitis/discitis was present in 5.4% in Group A and in none of Group B (p = 0.0096). The ratio of infectious spondylitis/discitis to other wound problems was 71% to 29% in Group A, while it was 0% to 100% in Group B (p = 0.0278). The mean time interval between the first revision surgery for wound complications and hospital discharge was significantly different, 38 days SD 20.3 in Group A and 14.4 days SD 8.6 in Group B (p = 0.0442).In our study, adherence to the GAID-Protocol resulted in a shift from severe to significantly less severe and easier to treat wound complications. Adoption of the GAID-Protocol might contribute to the reduction of implant-associated infections.